Recovering bioactive compounds and antioxidant capacity of medium roasted spent coffee grounds through varied hydrothermal brewing cycles - Nur Maiyah; Soraya Kerdpiboon; Suriyan Supapvanich; William L. Kerr; Pongsert Sriprom; Natthaporn Chotigavin; Wanwimol Klaypradit; Tongchai Puttongsiri (Journal of Agriculture and Food Research)
Spent coffee grounds (SCGs) are the residual product from brewing coffee and contain valuable bioactive compounds. This study investigated the effects of hydrothermal brewing cycles on the bioactive compounds and antioxidant capacity of medium roasted Arabica (A) and Robusta (R) SCGs. SCGs from A and R were prepared using 3 levels of brewing cycles at 92–95 °C/900 kPa. The SCGs were collected and air dried at 60 °C to achieve a moisture content of less than 4 % wb. Field emission scanning electron microscopy (FE-SEM) imaging showed that brewing increased SCGs porosity, allowing more moisture retention and enhanced extraction of compounds on subsequent cycles. SCGs also became less pigmented after additional brewing. Fourier-transform infrared (FTIR) spectra confirmed the retention of chemical components after each cycle, indicating a level of stability in the functional groups. Ethanol extraction yielded higher total phenolic content (TPC), while water extraction resulted in greater total flavonoid content (TFC); however, both decreased with additional hydrothermal brewing cycles. Caffeine and chlorogenic acid were more abundant in ethanol extracts, whereas water extracts exhibited stronger antioxidant activity (measured by ABTS and FRAP), particularly in Robusta SCGs. The bioactive compounds and antioxidant capacity were reduced with additional SCGs brewing. Significant correlations between TPC, TFC, caffeine, and antioxidant measures underscore the potential for the sustainable reuse of SCGs as a bioactive resource. Overall, hydrothermal brewing cycles enhanced the extraction and utilization of bioactive compounds from SCGs, contributing to the development of value-added products that promote health and sustainability.